Primerjava obnašanja regularnih in neregularnih konstrukcij pri potresni obremenitvi - Kilar, Vojko (AR. Arhitektura, raziskave, 2005)
Various regulations, demands, guidelines and recommendations stipulated in building legislature for construction in earthquake prone areas state the importance of regular building structures, both in layout and heights (which doesn't mean they are necessarily symmetrical). All larger discontinuity of vertical load-bearing elements, just as any significant changes in rigidity of particular floors, is seen as negative. Upon a review of contemporary building structures we can nevertheless establish that creativity in contemporary architectural expression usually refrains from using simple regular forms and likes to take recluse in forms, which are, from the structural attitude, irregular. Use of irregular structures is not strictly prohibited in regulations, but we have to be aware that such structures are in principal more expensive, less safe and consequentially less competitive.
Keywords: architecture; arhitektura; potresna varnost; potresno varna gradnja; konstrukcije; raziskave; potresna obremenitev